Effects of Long-term Storage on Seed Viability and Vigour of Wheat Germplasm under Ambient Conditions in Western Himalayas - RAJ PAL MEENA; P.R. KUMAR; J. KUMAR; RAGHUVEER SINGH; SUSHILA KUNDU (Seed Research, 2026)
A seed bank is a repository, where seeds are stored at low temperature and relative humidity to maintain their viability for longer durations without affecting their genetic integrity. A study was conducted at DWR, Regional Station, Dalang Maidan, Lahaul-Spiti (Himachal Pradesh) to explore the possibility of storage of wheat germplasm under ambient conditions. Investigation showed that germplasm stored for the last 12 years under ambient conditions maintained germination up to 81.9 per cent and high seedling vigour. The present paper deals with preservation of wheat germplasm for longer durations under ambient conditions of alpine climate of the Western Himalayas.